Electroretinographical determination of human color vision type - Aher, Avinash; Martins, Cristiane M. G.; Barboni, Mirella T. S.; Nagy, Balazs V.; Hauzman, Einat; Bonci, Daniela M. O.; Ventura, Dora F.; Kremers, Jan (Journal of the Optical Society of America A-Optics Image Science and Vision, 2018)
It has been previously demonstrated that electroretinography (ERG) elicited by heterochromatically modulated stimuli can be used for objective determination of color vision type. Color vision of trichromatic, deuteranopic, and protanopic participants was psychophysically assessed by the Cambridge Color Test and confirmed genetically. ERG responses to red and green lights modulating in counterphase at 12 and 36 Hz were recorded, while the fraction of red modulation was varied. At 36 Hz (and second harmonics at 12 Hz), the responses were minimal at red fractions that differed significantly in protanopes. At 12 Hz (fundamental component), the responses of the trichromats differed significantly compared to those of the dichromats. An improved protocol shows that the three subject groups can be separated with no overlap. (C) 2018 Optical Society of America